PENGARUH PROFITABILITAS TERHADAP NILAI PERUSAHAAN OTOMOTIF DI BURSA EFEK INDONESIA - Rosada, Fitrah Lia Amrina; Idayati, Farida (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
Profitability ratio is useful to demonstrate the success of the company in generating profits. When value of theprofitability of a company is getting high, it will attract the investors to invest their capital. When the stocks ofthe company are interested by investors, the firm value will increase. This research is aimed to find out theinfluence of profitability ratio which consists of Return on Assets, Return on Equity, Gross Profit Margin andNet Profit Margin to the firm value. The research is conducted on the automotive companies which are listed inIndonesia Stock Exchange. The data is the financial statements in 2010-2014 periods. The analysis technique hasbeen carried out by using multiple linear regressions analysis, F test and T test. The result of the research showsthat Return on Asset does not have any significant influence to the firm value of automotive companies whichare listed in Indonesia Stock Exchange, it can be seen from its significant value which is more than 0.05 that is0.083. Return on Equity has significant influence to the firm value of automotive companies which are listed inIndonesia Stock Exchange, it can be seen from its significant value which is less than 0.05 that is 0.021. GrossProfit Margin does not have any significant influence to the firm value of automotive companies which are listedin Indonesia Stock Exchange, it can be seen from its significant value which is more than 0.05 that is 0.181. NetProfit Margin does not have any significant influence to the firm value of the automotive companies which arelisted in Indonesia Stock Exchange, it can be seen from its significant value which is more than 0.05 is 0.300.Keywords: Return on assets, return on equity, gross profit margin, net profit margin, firm value